Deteksi Dini Karsinoma Sel Basal - SUKMAWATI TANSIL TAN; MAHMUD GHAZNAWIE; GABRIELA REGINATA (Indonesian Journal of Cancer, 2016)
ABSTRACTBasal Cell Carcinoma (BCC) is a malignant neoplasm derived from nonkeratinizing cells that originate in the basal layer of the epidermis, which is locally invasive, aggressive, destructive, and rarely metastasize. BCC is more common in the elderly. Etiopathogenesis associated with BCC is genetic, environmental, and most often is exposure to ultraviolet light. Clinically, there are five types of BCC, which are nodular, superficial, morpheaform, pigmented, and fibroepitelioma Pinkus. Early detection of skin cancer can be done with self skin examination. Definitive diagnosis of malignancy is determined by anatomical pathology examination. However, for very early BCC lesion, it’s difficult to determine with hematoxylin eosin staining. Therefore, it is uses Ber-EP4 staining which is specific and highly sensitive for early BCC growing as budding in basal layer of the epidermis and follicles. This finding is particularly significant in the development of molecular pathology and clinical management of BCC lesions or suspected BCC. ABSTRAKKarsinoma Sel Basal (KSB) merupakan neoplasma ganas dari sel yang tidak mengalami keratinisasi pada lapisan basal epidermis, bersifat invasif lokal, agresif, destruktif, dan jarang bermetastasis. KSB lebih sering terjadi pada usia lanjut. Etiopatogenesis yang berkaitan dengan KSB adalah genetik, lingkungan, dan yang paling sering adalah paparan sinar ultraviolet. Secara klinis, terdapat lima tipe KSB, yaitu nodular, superfisial, morpheaform, pigmented, dan fibroepitelioma Pinkus. Deteksi dini kanker kulit dapat dilakukan dengan pemeriksaan kulit sendiri (SAKURI). Diagnosis pasti keganasan ditentukan dengan pemeriksaan patologi anatomi. Namun, untuk lesi sangat dini KSB sulit ditentukan dengan pewarnaan hematoksilin eosin. Oleh karena itu, digunakanlah pewarnaan Ber-EP4 yang bersifat spesifik dan sangat sensitif untuk KSB dini yang tumbuh sebagai tunas di lapisan basal epidermis dan folikel. Temuan ini sangat berarti dalam pengembangan patologi molekuler dan penanganan klinis lesi KSB atau yang dicurigai KSB.